ANALISIS GEOKIMIA HIDROKARBON LAPANGAN “X” CEKUNGAN SUMATERA SELATAN - -, Budi Muljana (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
South Sumatra Basin belong to back-arc basin that is one of profiliferous basin. This paper was explained result of analysis of geochemical datas for source rocks within “X” field area, south Sumetra Basin. The data was used from shale cutting of four wells, there are KTB-6, KTB-9, KTB-10 and KTB -11. Based on result of analysis was indicated a good TOC value for all of wells, the levels of maturity within KTB-2 and KTB-9 wells more high than two wells other and included on Tipe III, Based on Triangular diagram C-27,C-28,C-29, are setting of depositional environment included on Open marine (facies deltaic) to shelf margin, source of organic material was divided into three major groups of organic facies, there are C, CD and D organic facies, where there was supported by Carbon isotop analysis, source of material organic from non marine oils as well as diagram isoprenoid rasio indicated. Rock units in KTB-9 well could be attacted as reservoir and source rock.